The Greek Experience: Outstanding Women in the Social Space of Sport - Irene Kamberidou; Chroni, Stiliani (Inspirational Women in Europe: making a difference in Physical Education, Sport and Dance, 2016)
The Voices of Six Inspirational Greek Women in Sport: What inspired them to take that leap; the Obstacles they faced; how they moved forward and Tips for Success.  Many inspirational and outstanding women have made a difference in the lives of girls and women in sport, physical education (PE) and physical activity in Greece, despite their invisibility in the mainstream media, the life stories of which would need volumes. They succeeded in making a difference while respecting and celebrating diversity with regard to gender, ethnicity, culture, disability, age and sexual orientation. Beginning with a brief discussion on the underrepresentation of women’s sports and the female athlete in the Greek media, this chapter shares the contributions of some inspiring and motivating Greek women in sport whose achievements have been excluded from the country’s mainstream media. It is through six in-depth interviews and follow-up meetings that we learn how these pioneers influenced the lives of sporting girls and women by daring to disregard social barriers and spread awareness. We conclude the chapter with tips from these successful, namely inspirational women, who all agree that success requires ethos and taking that leap. http://www.ngime.ufjf.br/wp-content/uploads/Europa_opt.pdf